PENGARUH PEMAHAMAN STANDAR AKUNTANSI PEMERINTAH DAN PEMANFAATAN SISTEM INFORMASI AKUNTANSI TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH DENGAN KOMPETENSI SDM SEBAGAI VARIABEL MODERASI (Studi Empiris Pada SKPD BPKAD Kabupaten Malang) - Sihasale, Debby Christin; Sulistyo, Sulistyo; Setiyowati, Supami Wahyu (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2018)
The purpose was to determine the effect of understanding government accounting standards (SAP) and Utilization of accounting information systems (SIA) on the quality of local government financial reports with HR competency as a moderating variable. The data used in the form of Primary data obtained through the distribution of questionnaires directly to the SKPD in BPKAD Malang Regency. Regression analysis used is multiple regression analysis with MRA (Moderating Regression Analysis). The results of this study concluded that the understanding of SAP and the use of SIA affect the quality of local government financial reports, and human resource competence is able to moderate (strengthen) the influence of SAP's understanding and the use of SIA on the quality of local government financial reports. The higher the competence of the government apparatus will support it in understanding and mastering SAP and making use of SIA well so that the quality of financial statements is increasingly improved. The implication is that the government must improve understanding of SAP and the use of SIA so that the quality of financial statements can improve, and it must involve officials who have competence to prepare financial reports so that the influence of SAP's understanding and use of SIA can improve the quality of local government financial reports